2020
DOI: 10.2337/dci20-0018
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Diabetes Prevention Interventions Targeting High-risk Individuals and Whole Populations: A Systematic Review

Abstract: OBJECTIVE We conducted a systematic review of studies evaluating the cost-effectiveness (CE) of interventions to prevent type 2 diabetes (T2D) among high-risk individuals and whole populations. RESEARCH DESIGN AND METHODS Interventions targeting high-risk individuals are those that identify people at high risk of developing T2D and then treat them with either lifestyle or metformin interventions. Population-based prevention s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 63 publications
3
79
1
3
Order By: Relevance
“…After 5.3 years of follow-up, CVD risk factors were modestly but significantly improved with intensive treatment compared with routine care, but the incidence of first CVD events or mortality was not significantly different between the groups (59). The screening has been reinforced in cohort studies (81,82). Additional considerations regarding testing for type 2 diabetes and prediabetes in asymptomatic patients include the following.…”
Section: Screening and Testing For Prediabetes And Type 2 Diabetes Inmentioning
confidence: 99%
“…After 5.3 years of follow-up, CVD risk factors were modestly but significantly improved with intensive treatment compared with routine care, but the incidence of first CVD events or mortality was not significantly different between the groups (59). The screening has been reinforced in cohort studies (81,82). Additional considerations regarding testing for type 2 diabetes and prediabetes in asymptomatic patients include the following.…”
Section: Screening and Testing For Prediabetes And Type 2 Diabetes Inmentioning
confidence: 99%
“…Moin and colleagues examined results from a trial of an online DPP found that an online DPP intervention achieved a similar weight loss goal compared to in-person DPP [ 19 ]. However, more research is needed to better understand the effectiveness and cost-effectiveness of virtual/on-line programs [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Community-based diabetes management has become a cost-effective and cost-saving strategy for controlling and managing diabetes in primary care settings. [2][3][4] The community-based intervention positively reduced the HbA1c level of diabetic people and improved lipids and blood pressure control [5][6][7][8] . In primary care and community settings, interventions targeting diabetes management were better targeted at individuals with poor glycemic control, old age, and family history of diabetes and cardiovascular diseases [9][10] .…”
Section: Introductionmentioning
confidence: 99%